Terceirização na gestão pública: limites e possibilidades jurídicas na gestão administrativa do poder judiciário - Fortuna, Débora Birello (2015)
The present dissertation approaches the theme of services outsourcing in the public management with focus on the limits and juridical possibilities of its use in the scope of the Judiciary. The aim is also to analyze the advantages of the usability in the scope of the Judiciary with regard to the costs reduction and efficiency raising. It will be approached the possibilities of the outsourcing usage, questioning, from the use of the inductive method, which would be the outsourced support activities, given the presence of ancillary functions. It will be identified, furthermore, the absence of legislation based on outsourcing, which promoted the importance of the use of the Precedent 331/TST as a normative reference for the framing of the outsourcing hypothesis. It will be employed the hypothetic-deductive method for the outsourcing analysis as an efficient tool of the administrative management of the Judiciary, questioning, therefore, its possible uses within the legal and constitutional parameters determined by the administrative legal regime. It´s expected to contribute to a bigger reflection on the efficiency paradigm of the Judiciary, from the analysis of the legal possibility of its administrative management.